The need for flexibility in forest harvesting services – a case study on contractors' workflow variations. Issue 1 (2nd January 2023) - Johansson, Malin; Erlandsson, Emanuel; Kronholm, Thomas; Lindroos, Ola
ABSTRACT: In many parts of the world, contractors account for the main share of harvesting work. Harvesting is characterized by innate complexity and volatility, and this can affect contractors' workflow and ultimately their profitability. Thus, there is certainly a need for flexibility in harvesting service provision and procedures, but our current knowledge about contractors' workflow variations are limited. This study investigates workflow variations in harvesting services by comparing monthly variations between contractors' workload in terms of harvested volumes and the time spent on operations. The data originates from 77 machines belonging to contractors and their harvesting of 6.6 million m 3 of roundwood in Sweden during a two-year period. The results indicate differences between contractors' workflow variations which can be attributed to the number of machines, machine sizes, and the workload in harvested volume and hours. These findings are relevant for guiding both the customer and contractor in this business relationship, and they could also serve as a basis for further research on the need for flexibility to effectively increase and decrease volume production in harvesting services.